1997
DOI: 10.1038/sj.ijir.3900281
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic taxonomy of treatments for erectile dysfunction: an evolutionary imperative

Abstract: Aim of the study: A functional classi®cation of treatments for erectile dysfunction is important but none exists at present. Advances in the understanding of the mechanisms of drug action and of the mechanisms of penile erection suggest that there is now a rational basis for a therapeutic classi®cation, with the expectation that a logical diagnostic classi®cation will follow.Methods: The currently available treatments for erectile function and the known relevant basic science were reviewed and assessed. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 12 publications
0
15
0
2
Order By: Relevance
“…Moreover, visual erotic stimulation (VES) was added to initiate erection. 4 Using an ATL HDI 1 5000 CV Duplex scanner, PPDU was performed as described by Meuleman et al 5 To assess arterial response we used peak¯ow velocity (PSV) and acceleration time (AT). To assess veno-occlusive response resistance index (RI) was calculated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, visual erotic stimulation (VES) was added to initiate erection. 4 Using an ATL HDI 1 5000 CV Duplex scanner, PPDU was performed as described by Meuleman et al 5 To assess arterial response we used peak¯ow velocity (PSV) and acceleration time (AT). To assess veno-occlusive response resistance index (RI) was calculated.…”
Section: Introductionmentioning
confidence: 99%
“…24 Heaton et al have proposed a therapeutic taxonomy and classified the treatments for erectile dysfunction into five classes: central initiator, peripheral initiator, central conditioner, peripheral conditioner, and other. 36 The results of this study showed that L-arginine may initiate penile erection through its action on a site (PVN) of CNS which may provide an academic basis to classify L-arginine as a central initiator. Accordingly, the implication of this experimental study was that L-arginine may be used clinically to induce penile erection through its action in the CNS.…”
Section: Discussionmentioning
confidence: 97%
“…20 Therefore, phentolamine should be considered as a conditioner (enhancer) of the erotic and=or nocturnal erections, rather than an initiator, improving the rigidity and duration of the erectile episodes. 21 Based on the results of our study, the question raised is can the available conditioners of the erectile process prevent ED, when administered before sleep for a long time period? Future studies will give the answer.…”
Section: Discussionmentioning
confidence: 99%